Exploration of Students' Engineering Thinking Skills Through STEM Integrated PjBL Model Design Water Rocket Momentum Material - Silvia Ainur Rohma; Rifati Dina Handayani; Albertus Djoko Lesmono (Berkala Ilmiah Pendidikan Fisika, 2024)
The research aims to analyse the engineering thinking skills of students by integrating the PjBL model with STEM water rocket design on momentum materials. This research is an experimental study. The design of this study was qualitative research. There are three stages to the research stage: preparation, implementation, and the final stage. The researchers collected data through observation, interviews, posttests, and documentaries. The focus of this study is on students' engineering thinking skills. The researchers interactively analyse the collected data during the phases of data collection, reduction, presentation, and conclusion. Additionally, the researchers conducted data credibility tests using triangulation techniques to assess the appropriateness of the research data. The research results predominantly classify the six indicators of engineering thinking as very good. Based on the findings and deductions, it is concluded that most students' engineering thinking abilities, when combined with the PjBL model and STEM water rocket design material, score highly on the six indicators of creative problem-solving. Students in this study experienced new knowledge and learning experiences that enabled them to solve daily problems by applying engineering thinking skills and physics concepts.